Postactivation potentiation as an ergogenic aid for sprint kayakers - Soh, Sze Ying (2016)
Postactivation potentiation (PAP) is a phenomenon that enhances acute muscular performance after a conditioning contraction. When a heavy resistance workout is performed prior to an exercise performance puts muscles in a potentiated state, which may enhance subsequent exercise performances. The purpose of this study is to find out whether kayak-specific resistance (KSR) can induce PAP to improve short kayak sprints. Ten participants (males, n=6; females, n=4) from the Singapore National Kayaking Team participated in the study. All participants first go through 1RM testing on the seated single-arm row machine. Thereafter, they went through an on-land determination of individualized PAP latency period with a preload protocol of 3 repetitions at 91% 1RM on the seated row machine before peak output measurements at 2, 4, 6, 8, 10, 12, 14, and 16 minutes. With the individualized rest interval obtained, participants underwent an on-water 30-m sprint with a KSR (using tennis balls) in the experimental condition (EXP) and no preload in the control condition (CON). Performance was measured with boat velocity at the 0-m and 30-m mark and 30-m sprint times. No significant differences in 30-m sprint times and boat velocity was observed between CON and EXP (p > 0.05). It was concluded that the KSR was not an effective PAP inducing tool to improve kayak sprint performance.